Switching from constant voltage to constant current in deep brain stimulation: a multicenter experience of mixed implants for movement disorders. (25th October 2015) - Preda, F.; Cavandoli, C.; Lettieri, C.; Pilleri, M.; Antonini, A.; Eleopra, R.; Mondani, M.; Martinuzzi, A.; Sarubbo, S.; Ghisellini, G.; Trezza, A.; Cavallo, M. A.; et al.
Abstract : Background and purpose: For many years deep brain stimulation (DBS) devices relied only on voltage‐controlled stimulation (CV), but recently current‐controlled devices have been developed and approved for new implants as well as for replacement of CV devices after battery drain. Constant‐current (CC) stimulation has been demonstrated to be effective in new implanted parkinsonian and dystonic patients, but the effect of switching to CC therapy in patients chronically stimulated with CV implantable pulse generators (IPGs) has not been assessed. This report shows the results of a consecutive retrospective data collection performed at five Italian centers before and after replacement of constant‐voltage with constant‐current DBS devices, in order to verify the clinical efficacy and safety of this procedure. Methods: Nineteen patients with Parkinson's disease or dystonic syndrome underwent DBS IPG CV/CC replacement. Clinical features and therapy satisfaction were assessed before surgery, 1 week after and 3 and 6 months after replacement. Programming settings and impedances were recorded before removing the CV device and when the CC IPGs were switched on. Results: The clinical outcome of CC stimulation was similar to that obtained with CV devices and remained stable at 3 and 6 months of follow‐up. Impedance values recorded for CV and CC IPGs were similar. Ninety‐five percent of patients and physicians were satisfied with mixed implants. No adverse events occurred after IPG replacement. Conclusion: Replacing CV with CC IPGs is a safe and effective procedure. Longer follow‐up is necessary to better clarify the impact of CC stimulation on clinical outcome after chronic stimulation in CV mode.